Auditory hallucinations in schizophrenia: Psychoeducation among caregivers to help patients develop effective coping strategies - Daryanto Daryanto; Mohammad Syukri; Sri Martini; Sri Endriyani; Mila Triana Sari (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Hallucinations are common symptoms experienced by patients with schizophrenia. These hallucinations pose difficulties in control, becoming a burden for caregivers providing care. Meanwhile, psychoeducation utilizing modules and videos to treat auditory hallucinations has not been previously implemented. Psychoeducation is beneficial in managing caregiver burden, yet the psychoeducation content hasn't been specific to auditory hallucinations.Purpose: To determine the influence of psychoeducation using modules and videos to help patients develop effective coping strategies, and burden among caregiversMethod: A quantitative study with a pre-experimental design using a pre-test and post-test approach. This research was conducted to measure caregiver burden before and after the intervention. The intervention involved providing psychoeducation using modules and videos for caring for auditory hallucinations, while the control group received psychoeducation using only modules. The study was conducted at the outpatient clinic of Jambi Regional Mental Hospital from July to September 2023.Results: There was a significant difference in caregiver burden (p-value 0.000) in the intervention group before and after treatment. There was a significant difference in caregiver burden (p-value 0.000) in the control group before and after treatment. There was no significant difference in caregiver burden (p-value 0.161) between the intervention and control groups one month after the intervention.Conclusion: Psychoeducation with modules and videos can reduce caregiver burden in schizophrenia patients. Psychiatric nurses should educate caregivers using modules and videos for caring for auditory hallucinations as part of reducing the caregiving burden.Suggestion: Healthcare professionals should also provide psychoeducation using auditory hallucination care modules and videos to caregivers on managing the caregiving burden for individuals with schizophrenia experiencing auditory hallucinations. Caregivers are encouraged to understand the module book and video on auditory hallucination care as a form of continued care at home for individuals with schizophrenia experiencing auditory hallucinations.